Pre-Marriage Course in Indonesia and Malaysia - Jamaluddin Faisal; Ahmad Tholabi Kharlie; Achmad Cholil (Universitas Islam Negeri Jakarta, 2020)
This study aims to compare the regulations of the Pre-Marriage Course and its implementation in Indonesia and Malaysia. Furthermore, this research seeks answers and a meeting point between the theory of maslahah and human rights in looking at the Pre-Marriage Course. This is a qualitative inquiry relying on a comprehensive literature study. The result indicates that the is no contradiction between the Pre-Marriage Course and the notion of mashalah and human rights. However, improvements and adjustment are still needed, which include sufficient infrastructures; professional organization; the commitment of future brides and grooms; as well as adequate financial supports. AbstrakPenelitian ini bertujuan untuk membandingkan aturan Kursus Pra-Nikah dan penerapannya di Indonesia dan Malaysia. Penelitian ini juga berupaya mencari jawaban dan menemukan titik temu antara teori maslahah dengan Hak Asasi Manusia dalam melihat Kursus Pra-Nikah. Penelitian ini merupakan penelitian kualitatif yang menekankan pada kajian literatur secara komprehensif. Dari kajian tersebut, ditemukan bahwa tidak ada pertentangan antara aturan dan praktik Kursus Pra-Nikah baik dengan teori maslahah maupun Hak Asasi Mansuia. Akan tetapi, masih ada beberapa hal yang perlu ditingkatkan dan disesuaikan yaitu kecukupan infrastruktur, pelaksanaan yang profesional, komitmen dari calon pengantin, dan kecukupan dukungan finansial.